Friction characteristics of trocars in laparoscopic surgery. (April 2015) - Alazmani, Ali; Roshan, Rupesh; Jayne, David G; Neville, Anne; Culmer, Peter
This article investigates the friction characteristics of the instrument–trocar interface in laparoscopic surgery for varying linear instrument velocities, trocar seal design and material, and trocar tilt. Furthermore, the effect of applying lubrication at the instrument–trocar seal interface on friction was studied. A friction testing apparatus was designed and built to characterise the resistance force at the instrument–trocar interface as a function of the instrument's linear movement in the 12-mm trocar (at constant velocity) for different design, seal material, and angle of tilt. The resistance force depended on the trocar seal design and material properties, specifically surface roughness, elasticity, hardness, the direction of movement, and the instrument linear velocity, and varied between 0.25 and 8 N. Lubricating the shaft with silicone oil reduced the peak resistance force by 75% for all trocars and eliminated the stick–slip phenomenon evident in non-lubricated cases. The magnitude of fluctuation in resistance force depends on the trocar design and is attributed to stick–slip of the sealing mechanism and is generally higher during retraction in comparison to insertion. Trocars that have an inlet seal made of rubber/polyurethane showed higher resistance forces during retraction. Use of a lubricant significantly reduced frictional effects. Comparisons of the investigated trocars indicate that a low friction port, providing the surgeon with improved haptic feedback, can be designed by improving the tribological properties of the trocar seal interface.